Biofilm Inhibition by Conventional Antibiotics Against Staphylococcus Aureus - Al. Qurabiy, Heyam Emad (American Journal of Biology and Natural Sciences, 2026)
Background: Staphylococcus aureus is a leading cause of chronic infections because of its biofilm-forming ability, which decreases antibiotic diffusion. The purpose of this study was to investigate the antibiofilm properties of selected conventional antibiotics against S. aureus and to compare their efficacy in preventing biofilm formation and disrupting established biofilms. Methods: S. aureus isolates (n = 20) were identified by standard microbiological procedures. Antibiotic susceptibility was evaluated by the Kirby-Bauer disk diffusion test, and the minimum inhibitory concentrations (MICs) were determined by the broth microdilution test. Biofilm-forming activity was screened by the 96-well microtiter plate crystal violet assay. The antibiofilm activity of conventional antibiotics (vancomycin, clindamycin, ciprofloxacin, gentamicin, and tetracycline) was evaluated at sub-MIC concentrations (0.25× and 0.5× MIC) for inhibiting biofilm formation and at 1× MIC for disrupting established biofilms after 24 hours. Percent inhibition/disruption was calculated compared to untreated controls. Statistical analysis was done by one-way ANOVA with p < 0.05. Results: Most isolates had moderate to strong biofilm-forming abilities (70%). Sub-MIC exposure resulted in a significant decrease in biofilm formation in a dose-dependent manner. When exposed to 0.5× MIC, clindamycin and ciprofloxacin had the greatest inhibition of biofilm formation (mean inhibition: 62% and 58%, respectively), followed by gentamicin (49%), tetracycline (45%), and vancomycin (38%) (p < 0.05). In pre-formed biofilms, antibiotic exposure at 1× MIC resulted in lower but significant disruption, with ciprofloxacin and gentamicin causing the greatest reduction in biofilm biomass (34% and 31%), while vancomycin caused the least disruption (18%). Inhibition of biofilm formation was consistently greater than disruption of mature biofilms. Conclusion: Conventional antibiotics showed detectable antibiofilm activity against S. aureus, especially in sub-inhibitory concentrations that inhibited biofilm formation. Mature biofilms, however, were much less susceptible, and this points to the importance of early targeted and/or combination therapy to enhance the eradication of established biofilm infections.